(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of using Powtoon-based animated video learning media on the learning interest in mathematics among fifth-grade students at SDN Cipari, Cigugur Subdistrict, Kuningan Regency in the 2025 academic year. The research employed a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The population and sample consisted of all 35 fifth-grade students. Data were collected through observation, interviews, questionnaires, and pretest–posttest assessments. The instruments were validated by media and subject matter experts, and reliability was tested using SPSS. Data analysis included validity, reliability, normality, and homogeneity tests, as well as paired t-tests. The results showed that the use of Powtoon animated videos had a significant positive effect on students’ interest in learning mathematics, as evidenced by the difference in mean scores before and after treatment in the experimental group compared to the control group. Furthermore, the student satisfaction questionnaire results were in the “very satisfied” category regarding the use of this media. Therefore, Powtoon-based animated video media is effective as an alternative learning method for mathematics that is engaging, interactive, and capable of increasing elementary school students learning interest.